Violation of the rights of sound record producers (piracy): A Comparative study - حسن, حيدر فليح; عبد الحسن, سلام هاشم (Journal of Legal Sciences, 2021)
Piracy is one of the most important problems faced by sound record producers, because it is a problem that evolves with the development of time and technology, and although piracy is not a new problem, it has received great attention in recent years, because of the means by which (the Internet) and its size result from it, even In many of the ruler, describing it as (the crime of the electronic age) and she participated in the great harm it causes to all the groups involved in it producing the sound recording, because there are three categories that contribute to the production of the sound recording, which is (the author of the recorded work, the artist who performs the work and the producer who performs an operation Performance recording and its transfer to and distribution of records), these three categories mentioned above are affected by the piracy process in general terms, the author and artist often have a certain percentage of the profits achieved by the sound recording, when piracy of this recording in any way, this will lead to the loss of a large part of the profits, And consequently the effect on the financial compensation mentioned by the three groups mentioned above is received.